2021
DOI: 10.1002/jmv.27449
|View full text |Cite
|
Sign up to set email alerts
|

First wave of COVID‐19 in Venezuela: Epidemiological, clinical, and paraclinical characteristics of first cases

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has particularly affected countries with weakened health services in Latin America, where proper patient management could be a critical step to address the epidemic. In this study, we aimed to characterize and identify which epidemiological, clinical, and paraclinical risk factors defined COVID-19 infection from the first confirmed cases through the first epidemic wave in Venezuela. A retrospective analysis of consecutive suspected cases of COVID-19 admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
2
3
1
Order By: Relevance
“…Early reports showed that the prevalence of cough during COVID-19 infection ranged from 44% to 72.5% [15], with a higher prevalence associated with Omicron variant infection than with Delta variant infection [4], although one survey from the United Kingdom [3] indicated that the prevalence of cough was similar between infections with the Omicron and Delta variants. In this study, the prevalence of cough was 92.6%, which was higher than that reported in previous studies [2][3][4]7], especially those based on data collected prior to emergence of the Omicron variant [16][17][18], suggesting that the prevalence of cough might be higher with the Omicron variant than with previous variants. In addition to cough, other symptoms such as fever, fatigue, myalgia, nasal congestion, and sore throat were also common, and over 60% of individuals reported having severe symptoms in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…Early reports showed that the prevalence of cough during COVID-19 infection ranged from 44% to 72.5% [15], with a higher prevalence associated with Omicron variant infection than with Delta variant infection [4], although one survey from the United Kingdom [3] indicated that the prevalence of cough was similar between infections with the Omicron and Delta variants. In this study, the prevalence of cough was 92.6%, which was higher than that reported in previous studies [2][3][4]7], especially those based on data collected prior to emergence of the Omicron variant [16][17][18], suggesting that the prevalence of cough might be higher with the Omicron variant than with previous variants. In addition to cough, other symptoms such as fever, fatigue, myalgia, nasal congestion, and sore throat were also common, and over 60% of individuals reported having severe symptoms in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…This is similar to our results.High oxygen saturation, a valuable metric for classifying disease severity, was associated with lower mortality rates in both groups under study. Conversely, low oxygen saturation has been identi ed as a signi cant indicator of mortality risk [47,74]. Additionally, the administration of enoxaparin, a low molecular weight heparin, was found to decrease mortality risk within our cohort, consistent with previous research [75, 76].…”
supporting
confidence: 91%
“…An increased risk of abortions and stillbirth in patients with COVID-19 has been described in larger studies [17,50,51], a pattern observed in our study with a higher proportion within the dead pregnant women, similar to that described in a Latin-American study [21], with the exception of the proportion of stillbirth. A possible hypothesis that could explain these discrepancies is poor antenatal care due to the collapse of health care centres during the COVID-19 pandemic in Venezuela, as well as quarantine and community containment measures [52]. Additionally, the retrospective nature of our study, which only included hospitalised pregnant women, and the limited access to routine screening for SARS-CoV-2 infection among pregnant women, may have contributed to this percentage difference in mortality.…”
Section: Discussionmentioning
confidence: 93%